Simple synchronisation technique for three-phase grid-connected distributed generation systems - Guo, Xiao-Qiang; Wu, Wei-Yang (IET renewable power generation, 2013)
Grid synchronisation is crucial for integration of renewable energy sources and distributed generation systems into the grid. Accurate and fast estimation of the fundamental positive sequence component is a necessity for synchronisation of three-phase distributed generation systems with the grid. In this study, a simple synchronisation technique based on the real-complex-coefficient filters is proposed. It has a very simple structure, and can directly estimate the fundamental positive and negative sequences under the distorted, unbalanced and offset conditions with no need of a phase-locked loop. Furthermore, the dc offset can also be extracted precisely. For optimising the steady-state and dynamic performance, a parameter tuning guidance is provided from the eigenvalue analysis point of view. In addition, a simple auxiliary unit is presented to remain its frequency-adaptive feature. Finally, experimental results based on a 32-bit fixed-point TMS320F2812 DSP verify the effectiveness of the proposed synchronisation method.